Factors Influencing Public Trust in Using a Digital Public Service Precision National Driving License (SINAR) in Indonesia - Nurhidayatullah Nurhidayatullah; Ulung Pribadi (Universitas Dharma Wacana, 2022)
The increasing influence of technology, information, and communication quickly, so that it can influence the role of government and institutions in implementing digital as a solution to speed up and provide convenience for the community. This study describes an empirical survey on public Trust using the digital precision driving license (SINAR) application. The presence of a precision national driving license application (SINAR) is a breakthrough to make it easier for the public to create and extend driving licenses online. This study tested four hypotheses: Public Trust in the presence of the SINAR application, Trust in information quality, security privacy, and regulation. The method uses quantitative research by distributing questionnaires and data analysis using SmartPLS 3. The results of hypothesis testing show that three hypotheses are rejected, including Trust in the quality of information, security, privacy, and regulation. While those that have been accepted or supported include public Trust in the application for a precision national driving license (SINAR). This proves that the community fully supports it because this application positively impacts society.